Development of Waste Bank Activities to Support the Citarum Harum - Rohmat, Dede; Nugraha, Diva; Setiawan, Iwan (Indonesia University of Education, 2021)
The Waste Bank is an effort to control pollution in the Citarum River. The development of the program needs to be monitored to see its sustainability. This study aims to examine the development of the Waste Bank around the Citarum River, in this case in the Bojongsoang and Dayeuhkolot Districts. The research method used a survey of the waste banks in the two districts. The research subject is the management of each Waste Bank. The results show that until 2018 there is a tendency for the number of Waste Banks to increase. However, the number of Waste Banks has decreased since 2019, even the number of Waste Banks in only one location is active in 2020.